VISION OF PHYSICAL THERAPISTS OF THE REGION AMURES AS A REQUEST FOR LABORATORY TESTS. (Fiep Bulletin - online, 2014)
Introduction: The diagnostic test ordering by the physiotherapist, is a right founded by Resolutions 80 and COFFITO CNE/CES4 by CBO and 2236. This prerogative, shows up relevant complementary tool to correct drafting the practice of physical therapy. Objective: To elucidate the vision of the region's AMURES physiotherapists as a diagnostic test ordering. Methodology: The survey was conducted with 123 professionals from 64 institutions connected to the physiotherapy sector located in the region of AMURES, using a self-administered questionnaire consisting of nine questions, in order to evaluate various aspects of design professionals as the prerogative of the request for additional tests. Results and Conclusion: The results of this study lead us to ensure that 70% of professionals are aware of the provisions of Article 3 of Res COFFITO 80 and 46% are aware of the provisions of Res CNE/CES4, Art.5 º , § VI, with 56% of the sample has already requested additional tests, where this percentage 46.4% showed good responsiveness to request additional tests. It was evident that even a good portion of the sample willing to ignore the specific law that grant request for additional tests, 90% declare themselves competent to request any kind of exams.
Keywords: Physiotherapists; AMURES; Supplementary Examinations